Percutaneous cystolithotripsy in children and its outcome: A single center experience - Joshi, Milind P; Ruturaj, Kakad; Pankaj, Chaudhari; Priti S, Zade; S, Gavai Mahendra; Ashwinikumar, Verma (Indian Journal of Child Health, 2018)
Background: Pediatric bladder stone disease is very common in certain regions of India. Traditionally, pediatric surgeons have been managing this by open surgeries. Aim: The aim of the study was to manage vesical calculus in children by percutaneous cystolithotripsy (PCCL). Materials and Methods: All the children up to 18 years of age suffering from vesical calculus were operated by PCCL. Cystoscopy performed first to assess the stone burden. 18 Fr angiocath needle was used to puncture the bladder under vision and 0.035 guide wire was passed. Tract was dilated using single-step screw dilator; a 20 French Amplatz sheath was passed over the screw dilator and nephroscope was introduced. Lithotripsy was done using pneumatic lithotripter. Per urethral Foley catheter was placed and suprapubic puncture site was suture closed. Results: A total of 74 patients were operated in the past 3 years with an age range was 1–18 years with female preponderance. Complete clearance was achieved in all patients while the average duration of surgery was 30 min with range of 15–50 min. All the patients were operated under regional anesthesia and were discharged the next day. Among the study population, three patients had superficial wound infections at the puncture site which was managed conservatively. Conclusion: PCCL is a good option for managing vesical calculus in children. It has minimal morbidity and very small scar as compared to open cystolithotomy. Even in recurrent stones, it can be effectively performed, and in fact, it is easy to learn and reproducible.